Music as Soft Power: The Electoral Use of Spotify - Raquel Quevedo-Redondo; Marta Rebolledo; Nuria Navarro-Sierra (Media and Communication, 2023)
The changes brought by new technologies and the ensuing rapid development of the communication field have resulted in an increasing number of studies on politicians’ use of the internet and social media. However, while election campaigns have been the predominant research area in political communication scholarship, music has not yet been taken as an object of study alongside spectacularisation and politainment. Aside from some preliminary studies, systematic research on music in politics is scarce. The literature holds that music is a universal language. Music in politics can therefore be deemed to be an identification tool that can help politicians connect with voters and bring together positions between the different actors of international relations. This is an exploratory study about the use of music in political campaigning. It is focused on the role played by the Spotify playlists created by the main political parties in recent election campaigns in Spain. The initial hypothesis is that some of the candidates strategically selected songs to be shared with their followers. A quantitative content analysis (N = 400) of some Spotify playlists showed that there were significant differences in the selection of songs among the different political parties. This research contributes to the understanding of how Spotify has been used for electoral campaigning, as well as shedding some light on the current communication literature on music and politics.